Incidência de Doenças Diarreicas Agudas no município de São Luís, Maranhão, Brasil - NUNES, Ana Tereza de Sousa (2017)
Acute diarrheal diseases, known as intestinal infectious diseases, stand out as a serious public health problem, especially in developing countries where they cause infant mortality; and are determined by socioeconomic, environmental, cultural and behavioral factors. This ecological research aimed to study the incidence of ADD in the municipality of São Luís – Maranhão state in Brazil, through the time series of cases reported between January 2012 and December 2015, by the Information System for Epidemiological Surveillance of Acute Diarrhea Diseases by the Municipal Secretariat of Health of São Luís. In the analyzed period, 58,043 cases of ADD were reported and spatialized in the seven sanitary districts of the city. Between the districts, Bequimão district occupied the first position in 2012 and 2015; and Coroadinho district in 2013 and 2014. However, there was a statistically significant difference in the mean ADD cases among the districts over the years studied. The age group most affected by the disease was among those older than 10 years (n = 33,206), followed by children 1 to 4 (n = 18,937), children less than one year (n = 8,556) and 5 to 9 (n = 6,548). Among the treatment plans used in the management of patients, plan C with 65.3% was the most used in all years, followed by plans A and B with respectively 24.2% and 9.9%. There is seasonality of the ADD, since the months of the highest precipitation, first semester of all years, corresponded to the increase in the incidence of the disease. There was a significant statistical correlation between the notified cases and areas of the sanitary districts with water supply and sewage collection network, indicating, therefore, the deficiency in the quality of both systems.